Strategi Pemanfaatan Media Sosial Instagram Sebagai Sarana Promosi Destinasi Wisata Desa Pandanrejo - Salsabila, Zalfa Hana Hayyun; Prathisara, Gibbran (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This research aims to make a significant contribution to the development of best practices for the promotion of Pandanrejo Village Tourism destinations (Dewa Pandan). Through a review of case studies and related literature, the formulation of the problem of this study is how to use Instagram social media as a promotional medium to increase visitor interest. This village, located in the Menoreh Hills Area, has won an award as the best tourist village in Central Java in 2023. Despite having diverse tourism potential, its digital promotion still faces various challenges that need to be optimized to increase visibility and tourist participation. In this study, the theory used includes communication strategies. This study applies a qualitative method with a case study approach and the STP (segmentation, targeting, positioning) method. Data was collected through observation, and interviews with tourism village managers, as well as analysis of Instagram social media content of Pandanrejo Tourism Village. The data analysis techniques used include data reduction, data presentation, and extraction with validation through source triangulation. The results of the study show that the use of Instagram as a means of promotion has a positive impact on increasing awareness and interest of tourists in Pandanrejo Tourism Village. Interactive and informative content, such as educational videos and tourist attraction promotions, has proven to be effective in attracting visitors. However, this study also found challenges in the consistency of social media management and the limitations of digital resources. Therefore, a more systematic and collaborative strategy is needed in managing digital promotion to support the development of sustainable tourism in this village.